Genesis of unification of EU law into national legislation of Ukraine in sphere of international road transport security - Stolyarskіy, Oleh (Migration & Law, 2024)
The article examines the problematic issues of the genesis of the unification of European Union Law into the national legislation of Ukraine in the field of ensuring the safety of international road transport. The main norms in this area were analyzed, and separate normative legal acts of Ukraine were identified, which reflect the consequences of the unification of the norms of the European Union in the sphere of ensuring the safety of international road transport. It is emphasized that in order to reduce the overloading of the transport infrastructure and the negative socio-economic consequences associated with it, as well as the general improvement of the efficiency and competitiveness of the transport sector, the European transport policy provides for the solution of the following main tasks: changing the ratio between different types of transport; development of interaction between different types of transport, intermodal transportation; elimination of natural obstacles that negatively affect the development of transportation due to the development of the main transport network and improvement of traffic management on it; financing the development of transport infrastructure; implementation of a set of measures to increase the safety of road transport (first of all, road safety); creation of effective payment mechanisms for the use of transport infrastructure, which provide compensation for the full costs of society; improvement of urban transport systems and increasing the stability of their functioning; carrying out measures aimed at mitigating the possible negative consequences of the expansion of the European Union; increasing the role of the European Union in the formation of new and improvement of existing mechanisms for ensuring international automobile safety in particular and transport policy in general.
Keywords: Genesis; Unification; EU Law; National legislation of Ukraine; Road transport; Security